Zinc-coated steel sheets, components and their manufacturing methods
A high-strength galvanized steel sheet with controlled steel structure and manufacturing process addresses hydrogen embrittlement and bendability issues, achieving improved tensile strength, yield ratio, and hydrogen embrittlement resistance for automotive use.
Patent Information
- Application Number
- JP2024512883
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-31
- Filing Date
- 2023-03-31
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2043-03-31
AI Technical Summary
Existing high-strength hot-dip galvanized steel sheets face issues with hydrogen embrittlement during manufacturing and processing, leading to potential cracking and deterioration of bendability, which are not adequately addressed by existing patent documents.
A galvanized steel sheet with a specific steel structure comprising less than 50% ferrite, 50% or more of martensite and bainite, 10% or less retained austenite, and 75% or more tempered martensite with controlled carbide precipitation, along with a manufacturing process that controls hydrogen trapping and release, ensuring a tensile strength of 980 MPa to 1470 MPa, yield ratio of 0.60 or more, and excellent bendability and hydrogen embrittlement resistance.
The solution provides a galvanized steel sheet with enhanced tensile strength, yield ratio, bendability, and hydrogen embrittlement resistance, suitable for automotive applications, by effectively trapping and reducing diffusible hydrogen through controlled carbide precipitation and manufacturing conditions.
Smart Images

Figure 0007613636000001 
Figure 0007613636000002 
Figure 0007613636000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-strength galvanized steel sheet having excellent formability, a member made of the high-strength galvanized steel sheet, and a method for producing the same. The galvanized steel sheet of the present invention is preferably used mainly as a steel sheet for automobiles. [Background technology]
[0002] In recent years, from the viewpoint of global environmental conservation, there has been a strong demand for improving fuel efficiency to reduce CO2 emissions from automobiles. Accordingly, there has been an active movement to reduce the weight of automobile bodies by thinning the body parts, and the need for high strength steel sheets, which are materials for automobile body parts. In particular, from the viewpoint of ensuring collision safety of automobiles, steel sheet materials used around the cabin are required to have not only high tensile strength but also high yield strength. In addition, it is necessary to have press formability so that the freedom of part shape is not lost due to high strength. Furthermore, if corrosion progresses during use as an automobile part, the original material strength may not be exhibited in the event of a collision, so the application of hot-dip galvanized steel sheets, which have excellent corrosion resistance, is expanding.
[0003] On the other hand, increasing the strength of steel sheets is accompanied by concerns about the occurrence of hydrogen embrittlement. Hydrogen embrittlement of high-strength steel sheets can be caused not only by hydrogen that invades from the outside due to corrosion during use, but also by hydrogen that invades during the manufacturing process. In particular, in the case of hot-dip galvanized steel sheets, a general method is to manufacture the steel sheets by continuously performing a series of processes from annealing to hot-dip galvanizing in a hydrogen-containing atmosphere in order to suppress reduction and oxidation of the steel sheets. For this reason, the galvanized layer is formed in a state in which hydrogen that invaded the steel from the atmosphere remains. Hydrogen diffusion during galvanization is very slow and acts as a barrier against the external release of diffusible hydrogen in the steel, so that diffusible hydrogen remains and hydrogen embrittlement during processing may promote cracking, and there is a risk of local ductility deterioration, especially bendability. Therefore, it is important to establish a hot-dip galvanized steel sheet with excellent hydrogen embrittlement resistance in which hydrogen in the steel is sufficiently reduced, and a manufacturing method thereof.
[0004] Regarding the problems related to the workability and hydrogen embrittlement resistance of high-strength hot-dip galvanized steel sheets, for example, Patent Document 1 discloses a high-strength hot-dip galvanized steel sheet with excellent bendability and a manufacturing method thereof. Also, Patent Document 2 discloses a high-strength steel sheet of TS900 MPa or more with excellent ductility and delayed fracture resistance, a manufacturing method of a high-strength cold-rolled steel sheet, and a manufacturing method of a high-strength galvanized steel sheet. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2016 / 113788 [Patent Document 2] JP 2011-111671 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, while Patent Document 1 describes the improvement of bendability by refining martensite grains, it does not disclose a method for improving hydrogen embrittlement resistance. Also, Patent Document 2 describes the compatibility of ductility and hydrogen embrittlement resistance, but deals with hydrogen embrittlement resistance after processing, and does not describe the improvement of hydrogen embrittlement resistance caused by hydrogen that enters the steel during manufacturing. It is believed that the manufacturing methods disclosed in these patent documents result in a large amount of hydrogen remaining in the steel, which poses a risk of hydrogen embrittlement occurring during the processing, such as deterioration of bendability and cracking in nuggets of spot welds.
[0007] The present invention has been made in view of the above circumstances, and provides a galvanized steel sheet, a member, and a manufacturing method thereof, which are suitable for automotive applications and have a high yield ratio (YR), excellent bendability, and excellent hydrogen embrittlement resistance, and a tensile strength (TS) of 980 MPa or more and less than 1470 MPa.
[0008] In this case, a high yield ratio means that a JIS No. 5 tensile test piece (JIS Z2201) is taken perpendicular to the rolling direction and the strain rate is increased to 10 -3 This indicates that the YR is 0.60 or more when a tensile test is conducted in accordance with the provisions of JIS Z2241 (2011) for Yield Strength / s.
[0009] Tensile strength (TS) was measured by taking JIS No. 5 tensile test pieces (JIS Z2201) perpendicular to the rolling direction and increasing the strain rate to 10 -3 This refers to the tensile strength obtained by conducting a tensile test in accordance with the provisions of JIS Z2241 (2011) at 100 / s.
[0010] Excellent bendability refers to a condition in which a rectangular test piece of 35 mm x 100 mm is taken from a galvanized steel sheet so that the direction parallel to the rolling direction is the bending test axis, and a 90-degree V-bend test is performed with various bending radii at a stroke speed of 50 mm / s, a pressing load of 10 ton, and a pressing hold time of 5 seconds. The ridgeline at the bent apex of the test piece is observed with a 10x magnifying glass, and R / t, which is the minimum bending radius R (mm) at which no cracks of 0.5 mm or more in length were observed, is calculated by dividing the value by the sheet thickness (mm), and the result satisfies any of the following (A), (B), or (C). (A) TS: 980MPa or more but less than 1100MPa and R / t: 5.0 or less (B) TS: 1100MPa or more but less than 1300MPa and R / t: 6.0 or less (C) TS: 1300MPa or more but less than 1470MPa and R / t: 7.0 or less
[0011] "Excellent resistance to hydrogen embrittlement" means that when spot welding is performed using the following method, the cracks in the resulting nugget are 100 μm or less. (1) A 30 mm x 100 mm test piece was taken from a galvanized steel plate. A 2 mm thick spacer was placed on both ends of the test piece, and the center between the spacers was spot welded to prepare a welded test piece. (2) For spot welding, an inverter DC resistance spot welding machine is used, and the electrode is a dome-shaped chromium copper electrode with a tip diameter of 6 mm. The pressure is 380 kgf, the current flow time is 16 cycles / 50 Hz, and the holding time is 5 cycles / 50 Hz. (3) The welding current value is adjusted so as to form a nugget diameter according to the TS. The nugget diameter shall be 3.8 mm when TS is 980 MPa or more and less than 1250 MPa, and 4.8 mm when TS is 1250 MPa or more and less than 1470 MPa. (4) After leaving the spot welded for 24 hours, the spacer portion is cut off and the cross section of the nugget is observed. [Means for solving the problem]
[0012] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that it is possible to reduce diffusible hydrogen in steel by optimizing the steel sheet structure and appropriately controlling the precipitation morphology of carbides in the steel and utilizing them as hydrogen trapping sites, thereby making it possible to obtain a high-strength galvanized steel sheet that has a high yield ratio, excellent bendability, and a low risk of cracking in the nugget of a spot weld.
[0013] The present invention was made based on these findings, and the gist of the present invention is as follows. [1] A galvanized steel sheet having a base steel sheet and a galvanized layer formed on a surface of the base steel sheet, The base steel sheet is In terms of area ratio, Ferrite: less than 50% The sum of martensite and bainite: 50% or more, A steel structure having a retained austenite content of 10% or less, In terms of area ratio, 75% or more of the martensite is tempered martensite having carbides having an average grain size of 50 nm or more and 200 nm or less; The ratio TM1 / TM2 between the area fraction TM1 of tempered martensite in the entire structure in the region from the surface to 1 / 8 of the sheet thickness and the area fraction TM2 of tempered martensite in the entire structure in the region from 1 / 8 to 3 / 8 of the sheet thickness is 0.70 or more; The tensile strength is 980 MPa or more and less than 1470 MPa, The yield ratio is 0.60 or more, A zinc-plated steel sheet, in which the integrated amount of hydrogen released when the base steel sheet from which the zinc-plated layer has been peeled off is heated from room temperature to 200°C is 0.45 mass ppm or less. [2] The steel composition of the base steel sheet is, in mass%, C: 0.080% or more and 0.300% or less, Si: 0.01% or more and 2.00% or less, Mn: 1.00% or more and 4.00% or less, P: 0.10% or less, S: 0.0200% or less, Al: 0.003% or more and 0.100% or less, N: Contains 0.0100% or less, The zinc-plated steel sheet according to [1] above, wherein the balance consists of Fe and unavoidable impurities. [3] The steel composition further comprises, in mass%, B: 0.0100% or less, Ti: 0.200% or less, Nb: 0.200% or less, Sb: 0.200% or less, Sn: 0.200% or less, V: 0.100% or less, Cu: 2.00% or less, Cr: 2.00% or less, Ni: 2.00% or less, Mo: 1.00% or less Ta: 0.100% or less, W: 0.500% or less, Zr: 0.020% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Zn: 0.020% or less, Co: 0.020% or less, Ce: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0200% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less and REM (excluding Ce): At least one selected from below 0.0200% The zinc-plated steel sheet according to [2] above, which contains [4] The galvanized steel sheet according to any one of the above [1] to [3], wherein the galvanized layer is a galvannealed layer. [5] The galvanized steel sheet according to any one of [1] to [4] above, wherein when the base steel sheet from which the galvanized layer has been peeled off is heated from room temperature to 600°C, the integrated amount of hydrogen released in a temperature range of 350 to 600°C is 0.05 ppm by mass or more. [6] A member made using the zinc-plated steel sheet according to any one of [1] to [5] above. [7] A hot rolling process in which a slab having the steel composition described in [2] or [3] is heated to a temperature range of 1100 to 1350 ° C, hot rolled at a finish rolling end temperature of 800 to 950 ° C, and coiled at a coiling temperature of 650 ° C or less; An oxidation process in which the steel sheet after the hot rolling process is heated to 600° C. or higher in an oxidizing atmosphere containing an oxygen concentration of 1000 ppm by volume or more and 30000 ppm by volume or less; A reduction process in which the steel sheet after the oxidation process is held in a reducing atmosphere at 700°C or higher, with a dew point of -20°C or lower and a hydrogen concentration of 8% by volume or more and 30% by volume or less, for 20 seconds or more; a soaking step of holding the steel sheet after the reduction step in a soaking atmosphere at 750°C or higher, with a dew point of -20°C or lower and a hydrogen concentration of 0.2% by volume or more and 8% by volume or less, for 20 s to 300 s; A first cooling step of cooling the steel sheet after the soaking step; a galvanizing step of forming a galvanized layer on the surface of the steel sheet after the first cooling step; a second cooling step in which the steel sheet after the galvanizing step is cooled from a temperature range of 350 to 450°C to (Ms point - 100°C) at an average cooling rate of 20°C / s or less and is retained in a temperature range of 100 to 200°C for 5 seconds or more to a cooling stop temperature of 100°C or less; A reheating process in which the steel sheet after the second cooling process is held at a temperature range of 100 to 450 ° C. for 5 to 600 s; A method for producing a galvanized steel sheet, comprising: [8] The method for producing a zinc-plated steel sheet according to [7], wherein after the zinc plating step, the zinc plating layer is formed on the surface of the steel sheet, and then an alloying treatment is further performed. [9] A method for producing a galvanized steel sheet according to [7] or [8], comprising a cold rolling step of cold rolling at a reduction rate of 20% or more after the hot rolling step and before the oxidation step.
[10] The method for producing a galvanized steel sheet according to any one of [7] to [9], wherein in the first cooling step, the steel sheet after the soaking step is cooled from 600 to 900°C to 150 to 500°C at an average cooling rate of 20°C / s or less in an atmosphere with a hydrogen concentration of 0.5 vol% or more and 30 vol% or less and a dew point of 0°C or less.
[11] The method for producing a galvanized steel sheet according to any one of [7] to
[10] above, wherein in the second cooling step, the average cooling rate from the temperature range of 350 to 450°C to (Ms point - 100°C) is 10°C / s or less, and the steel is allowed to remain in the temperature range of 100 to 200°C for 10 seconds or more to cool to a cooling stop temperature of 100°C or less.
[12] A method for producing a component, comprising the step of subjecting the zinc-plated steel sheet according to any one of [1] to [5] above to at least one of forming and joining to produce a component. Effect of the Invention
[0014] The galvanized steel sheet provided by the present invention has a tensile strength of 980 MPa or more and less than 1470 MPa, a yield ratio of 0.60 or more, and is excellent in bendability and resistance to hydrogen embrittlement. Furthermore, the member provided by the present invention has a tensile strength of 780 MPa or more and less than 1180 MPa, a yield ratio of 0.60 or more, and is excellent in bendability, stretch flangeability, and resistance to hydrogen embrittlement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below.
[0016] <Zinc-plated steel sheet> The galvanized steel sheet of the present invention is a galvanized steel sheet having a base steel sheet and a galvanized layer formed on a surface of the base steel sheet, wherein the base steel sheet has a steel structure in which, in area ratios, ferrite is less than 50%, the sum of martensite and bainite is 50% or more, and retained austenite is 10% or less, and, in area ratios, 75% or more of the martensite has carbides having an average grain size of 50 nm or more and 200 nm or less, TM1 / TM2, which is a ratio of the area ratio TM1 of tempered martensite in the entire structure in a region from the surface to 1 / 8 of the sheet thickness to the area ratio TM2 of tempered martensite in the entire structure in a region from 1 / 8 to 3 / 8 of the sheet thickness, is 0.70 or more, the tensile strength is 980 MPa or more and less than 1470 MPa, the yield ratio is 0.60 or more, and the integrated value of the amount of hydrogen released when the temperature of the base steel sheet from which the galvanized layer has been peeled off is raised from room temperature to 200°C is 0.45 mass ppm or less.
[0017] steel structure First, the area ratio of each structure in the base steel sheet of the present invention will be described. The area ratio of each structure refers to the area ratio of each constituent phase to the total area observed. The area ratio of each structure can be determined from image data obtained by polishing a steel sheet cross section parallel to the rolling direction, corroding it with a nital solution, and photographing it at a magnification of 1500 times with a SEM (scanning electron microscope). The measurement areas are a region 1 / 8 of the sheet thickness from the surface and a region 1 / 8 to 3 / 8 of the sheet thickness. In the image data, ferrite is black, bainite is black with island-like retained austenite or gray with aligned carbides, tempered martensite is light gray with fine randomly oriented carbides, and retained austenite is white. Here, as-quenched martensite and retained austenite are both white, so they can be difficult to distinguish from SEM images. For this reason, the area fraction of retained austenite is determined individually by measuring the X-ray diffraction intensity, and the area fraction of as-quenched martensite is calculated by subtracting it from the area fraction of the white area mentioned above. The area fraction of retained austenite is calculated from the ratio of the X-ray diffraction integrated intensity of the (200), (220), and (311) planes of fcc iron to the X-ray diffraction integrated intensity of the (200), (211), and (220) planes of bcc iron at 1 / 4 of the plate thickness. The retained austenite is calculated as a volume fraction by the above measurement, but the retained austenite is considered to be three-dimensionally homogeneous, and the volume fraction of the retained austenite is taken as the area fraction of the retained austenite. The martensite defined in the present invention includes both as-quenched martensite and tempered martensite, and may consist of as-quenched martensite and tempered martensite.
[0018] Ferrite area ratio: less than 50% The presence of ferrite is advantageous for improving ductility, but is disadvantageous for obtaining high TS and high yield ratio. If the area ratio of ferrite is 50% or more, a TS of 980 MPa or more may not be obtained. Therefore, the area ratio of ferrite is less than 50%, and preferably less than 45%. The lower limit is not particularly limited, and the area ratio of ferrite may be 0%, but is preferably 1% or more, and more preferably 2% or more.
[0019] Total area ratio of martensite and bainite: 50% or more Martensite is a hard structure that is generated from austenite at a low temperature below the martensite transformation start point (Ms point). In the present invention, martensite includes not only as-quenched martensite (as-quenched martensite) but also tempered martensite obtained by tempering the generated martensite at a predetermined temperature. Bainite is formed from austenite at a relatively low temperature equal to or higher than the Ms point, and is a hard structure in which fine carbides are dispersed in needle-like or plate-like ferrite. Martensite and bainite are structures that contribute to the strength of the steel plate of the present invention, and if the total area ratio is less than 50%, a TS of 980 MPa or more may not be obtained. Therefore, the total area ratio of martensite and bainite is 50% or more, and preferably 55% or more. The total area ratio of martensite and bainite may be 100%, or only one of them may be within the above range.
[0020] Area ratio of retained austenite: 10% or less The retained austenite may transform into hard martensite during bending and promote crack generation, and this effect becomes significant when the retained austenite exceeds 10%. Therefore, the area ratio of the retained austenite is 10% or less, and preferably 5% or less. The retained austenite may be 0%.
[0021] As long as the contents of ferrite, martensite, bainite and retained austenite satisfy the above ranges, the remaining structure may contain other structures at an area ratio of 5% or less. Examples of other structures include pearlite.
[0022] Area ratio: 75% or more of martensite: Tempered martensite with carbides having an average grain size of 50 nm or more and 200 nm or less In the present invention, a high yield ratio is obtained by controlling the area ratio of the entire martensite contained in the structure to be 75% or more of tempered martensite having carbides of a predetermined size. At the same time, it is possible to achieve both hydrogen embrittlement resistance and hydrogen embrittlement resistance by utilizing fine carbides as hydrogen trapping sites in the steel and reducing diffusible hydrogen. In order to fully obtain these effects, the area ratio of tempered martensite in the entire martensite is 75% or more, preferably 80% or more, and may be 100%. This effect is obtained by setting the carbide size to a range of average grain size of 50 nm or more and 200 nm or less. In general, when the volume ratio of precipitates is constant, the smaller the grain size of the precipitates, the more advantageous it is for precipitation strengthening. In addition, from the viewpoint of hydrogen trapping, the larger the surface area of the carbides, the more advantageous it is, so that when the volume ratio is constant, the smaller the grain size of the carbides, the more preferable it is. Furthermore, when the carbides become coarse, it causes deterioration of bending properties. Therefore, the average grain size of the carbides is 200 nm or less. On the other hand, if the carbide grain size is less than 50 nm, the volume fraction of the carbide decreases, and the effects of precipitation strengthening and hydrogen trapping required for the present invention may not be sufficiently obtained. Therefore, the average grain size of the carbide is 50 nm or more. Here, the average particle size is the average value of the major axis length and the minor axis length when the particle is approximated as an ellipse. The average particle size can be measured by the method shown in the Examples, for example.
[0023] The ratio of the area fraction TM1 of tempered martensite in the entire structure in the region from the surface to 1 / 8 of the plate thickness to the area fraction TM2 of tempered martensite in the entire structure in the region from 1 / 8 to 3 / 8 of the plate thickness is TM1 / TM2: 0.70 or more In the galvanized steel sheet of the present invention, TM1 / TM2, which is the ratio of the area fraction TM1 of tempered martensite in the entire structure in the region from the steel sheet surface to 1 / 8 of the sheet thickness (hereinafter also referred to as the steel sheet surface layer portion) to the area fraction TM2 (vol%) of tempered martensite in the entire structure in the region from 1 / 8 to 3 / 8 of the sheet thickness, must be 0.70 or more. If TM1 / TM2 is less than 0.70, the effect of the carbides in the steel sheet surface layer portion is insufficient, and it may not be possible to achieve both a high yield ratio and excellent bendability. Therefore, TM1 / TM2 is set to 0.70 or more, preferably 0.72 or more, and more preferably 0.75 or more. The upper limit is not particularly limited and may be 1.00. The surface (steel sheet surface) referred to here refers to the surface of the base steel sheet (base steel, base steel sheet) beneath the zinc-plated layer.
[0024] For TM1 and TM2, a cross section of the plate parallel to the rolling direction is polished, then corroded with nital solution, and the structure is photographed with an SEM at a magnification of 1500x in three or more fields of view in the region from the surface to 1 / 8 of the plate thickness and in the region from 1 / 8 to 3 / 8 of the plate thickness. TM1 / TM2 is then calculated from the area ratio of the tempered martensite obtained.
[0025] The cumulative amount of hydrogen released when the base steel sheet from which the zinc-coated layer has been peeled off is heated from room temperature to 200°C: 0.45 mass ppm or less In the galvanized steel sheet of the present invention, by controlling the carbides in martensite to fall within the above-mentioned range, hydrogen that has entered the steel during the manufacturing process is effectively trapped, thereby reducing diffusible hydrogen and providing excellent bendability and hydrogen embrittlement resistance. In the present invention, the amount of diffusible hydrogen in steel is defined as the integrated value of the amount of hydrogen released when the base steel sheet from which the plating layer has been peeled off is heated from room temperature (15 to 35°C) to 200°C at a rate of 200°C / h. If the diffusible hydrogen content exceeds 0.45 ppm by mass, excellent bendability and hydrogen embrittlement resistance may not be obtained, and therefore the diffusible hydrogen content is 0.45 ppm by mass or less, and preferably 0.40 ppm by mass or less. The lower limit is not particularly limited, but since the smaller the amount of diffusible hydrogen, the more preferable, it may be set to 0 ppm by mass.
[0026] When the base steel sheet from which the zinc-coated layer has been peeled off is heated from room temperature to 600°C, the cumulative amount of hydrogen released in the temperature range of 350°C to 600°C is 0.05 mass ppm or more (optimal conditions) The galvanized steel sheet of the present invention is designed to reduce diffusible hydrogen by effectively trapping hydrogen that has entered the steel during the manufacturing process by controlling the amount of carbides in the martensite to fall within the above-mentioned range. Hydrogen trapped in the carbides is less likely to be desorbed from the steel than diffusible hydrogen, and is not released by heating up to 200°C, but is released at 350°C or higher. In order to fully obtain the effects of the present invention, when a steel sheet from which the plating layer has been peeled off is heated from room temperature (15 to 35°C) to 600°C at a rate of 200°C / h, the integrated value of hydrogen released at 350 to 600°C (trapped hydrogen amount) is preferably 0.05 mass ppm or more. More preferably, it is 0.07 mass ppm or more. There is no particular upper limit, but the integrated value of the amount of hydrogen released at 350 to 600° C. may be 1.00 mass ppm or less.
[0027] The above-mentioned method for quantifying hydrogen in steel involves taking a test piece for hydrogen analysis measuring about 5 x 30 mm from a galvanized steel sheet, removing the galvanized layer from the surface using a precision grinder, quickly placing it in a quartz tube whose atmosphere has been replaced with Ar gas, heating it to 600°C at a heating rate of 200°C / h, and measuring the amount of hydrogen released during heating using a gas chromatograph. The integrated value of the amount of hydrogen released in the temperature range from room temperature to 200°C is calculated as the "amount of diffusible hydrogen," and the integrated value of the amount of hydrogen released in the temperature range from 350°C to 600°C is calculated as the "amount of trapped hydrogen." Here, the measurement of the amount of hydrogen is preferably carried out after the manufacturing of the steel sheet is completed. That is, the measurement of the amount of diffusible hydrogen is preferably carried out after the manufacturing of the steel sheet is completed. Also, the measurement of the amount of trapped hydrogen is preferably carried out after the manufacturing of the steel sheet is completed. Furthermore, it is more preferable that the measurement of the amount of diffusible hydrogen and the amount of trapped hydrogen be carried out within 72 hours after the steel sheet first reaches room temperature (40° C. or lower) after the reheating step specified in the present invention.
[0028] Zinc plating layer The galvanized steel sheet of the present invention has a galvanized layer on the surface of a base steel sheet, and the galvanized layer may be a galvannealed layer, a hot-dip galvanized layer, or an alloyed hot-dip galvanized layer. This galvanized layer may be provided on only one surface of the base steel sheet, or on both surfaces.
[0029] The galvanized layer referred to here refers to a plating layer whose main component is Zn (Zn content of 50.0% or more), and examples thereof include a galvanized layer such as a hot-dip galvanized layer and an alloyed galvanized layer such as an alloyed hot-dip galvanized layer.
[0030] Here, the hot-dip galvanized layer (galvanized layer) is preferably composed of, for example, Zn, 20.0 mass% or less of Fe, and 0.001 mass% to 1.0 mass% of Al. The hot-dip galvanized layer may optionally contain one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM in a total amount of 0.0 mass% to 3.5 mass%. The Fe content of the hot-dip galvanized layer is more preferably less than 7.0 mass%. The remainder other than the above elements is unavoidable impurities.
[0031] In addition, the galvannealed layer (galvannealed layer) is preferably composed of, for example, 20% by mass or less of Fe and 0.001% by mass or more and 1.0% by mass or less of Al. In addition, the galvannealed layer may optionally contain one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi and REM in a total amount of 0.0% by mass or more and 3.5% by mass or less. The Fe content of the galvannealed layer is more preferably 7.0% by mass or more, and more preferably 8.0% by mass or more. The Fe content of the galvannealed layer is more preferably 15.0% by mass or less, and more preferably 13.0% by mass or less. The remainder other than the above elements is unavoidable impurities.
[0032] In addition, the coating weight of the zinc-plated layer on one side is not particularly limited, but is preferably 20 g / m 2 The coating weight of the zinc-plated layer on one side is preferably 80 g / m or more. 2 It is preferable that:
[0033] The plating weight of the zinc plating layer is measured as follows. That is, a treatment solution is prepared by adding 0.6 g of a corrosion inhibitor for Fe (Ivit 700BK (registered trademark) manufactured by Asahi Chemical Industry Co., Ltd.) to 1 L of a 10 mass % aqueous hydrochloric acid solution. Next, a steel sheet to be used as a test material is immersed in the treatment solution to dissolve the zinc plating layer. The amount of mass loss of the test material before and after dissolution is then measured, and this value is divided by the surface area of the base steel sheet (the surface area of the part that was covered with plating) to obtain the plating coverage (g / m 2 ) is calculated.
[0034] Ingredient composition Next, a preferred composition of the steel sheet (base steel sheet (hereinafter, sometimes simply referred to as steel sheet)) constituting the galvanized steel sheet will be described. Note that "%" representing the content of the component elements means "mass %" unless otherwise specified.
[0035] C: 0.080% or more and 0.300% or less C improves hardenability and makes it easier to obtain martensite and bainite. In addition, by precipitating in the structure as fine carbides, it is possible to trap hydrogen in the steel, reducing the amount of diffusible hydrogen and improving bendability. If the C content is less than 0.080%, it is not possible to satisfy all of TS≧980MPa, yield ratio: 0.60 or more, and excellent bendability. Therefore, the C content is preferably 0.080% or more, and more preferably 0.100% or more. On the other hand, if the C content exceeds 0.300%, the hydrogen trapping effect of fine carbides becomes saturated, and the strength of martensite becomes excessively high, which may impair bendability. Therefore, the C content is preferably 0.300% or less, and more preferably 0.250% or less.
[0036] Si: 0.01% or more and 2.00% or less Silicon is an element that is effective in strengthening ferrite, which has excellent ductility, and contributes to improving the balance between strength and ductility. If the silicon content is less than 0.01%, this effect cannot be obtained. Therefore, the silicon content is preferably 0.01% or more, and more preferably 0.1% or more. On the other hand, Si is also an element that suppresses the formation of carbides. If the Si content exceeds 2.00%, the formation of carbides necessary for the present invention is suppressed, and excellent bendability may not be obtained. Therefore, the Si content is preferably 2.00% or less, and more preferably 1.50% or less.
[0037] Mn: 1.00% or more and 4.00% or less Mn improves the hardenability of steel, making it easier to obtain martensite and bainite. If the Mn content is less than 1.00%, the area ratio of ferrite becomes excessive, and the required strength and yield ratio may not be obtained. Therefore, the Mn content is preferably 1.00% or more, and more preferably 1.50% or more. On the other hand, if the Mn content exceeds 4.00%, the strength of martensite becomes excessively high, and the formation of coarse MnS is promoted, so that excellent bendability may not be obtained. Therefore, the Mn content is preferably 4.00% or less, and more preferably 3.50% or less.
[0038] P:0.10% or less If P is contained in excess, it segregates at the prior austenite grain boundaries, embrittling the grain boundaries and causing deterioration of bendability. Therefore, the P content is preferably 0.10% or less, and more preferably 0.05% or less. The P content is preferably 0.03% or less, and more preferably 0.02% or less. Although there is no particular lower limit, since P is also an element effective in increasing the strength of the steel sheet by solid solution strengthening, in order to obtain such an effect, the P content is preferably 0.001% or more. The P content may be 0.002% or more, or may be 0.005% or more.
[0039] S: 0.0200% or less S forms inclusions such as MnS and causes deterioration of bendability, so the S content is preferably 0.0200% or less, and more preferably 0.0100% or less. Although there is no particular lower limit, due to constraints on production technology, the S content may be 0.0001% or more, may be 0.0002% or more, or may be 0.0004% or more.
[0040] Al: 0.003% or more and 0.100% or less In addition to being used as a deoxidizer, Al also contributes to solid solution strengthening of steel. If the Al content is less than 0.003%, these effects may not be obtained. Therefore, the Al content is preferably 0.003% or more. The Al content is preferably 0.005% or more, and more preferably 0.007% or more. On the other hand, if the Al content exceeds 0.100%, it leads to deterioration of slab quality during steelmaking, so the Al content is preferably 0.100% or less, and more preferably 0.050% or less.
[0041] N: 0.0100% or less N may form coarse nitrides, which may become the starting point for void generation and reduce bendability. By setting the N content to 0.0100% or less, it is possible to prevent N from forming coarse nitrides. Therefore, the N content is preferably 0.0100% or less, and more preferably 0.0060% or less. Although there is no particular lower limit, due to constraints on production technology, the N content may be set to 0.0005% or more.
[0042] The balance other than the above consists of Fe and unavoidable impurities.The steel sheet of the present invention preferably has a composition containing the above-mentioned components with the balance consisting of Fe and unavoidable impurities. The composition may further contain a predetermined amount of at least one element selected from the following group of elements. When the following optional elements are contained in an amount less than the preferred lower limit, the optional elements can be regarded as being contained as unavoidable impurities.
[0043] B: 0.0100% or less B is an element effective in improving the hardenability of steel. In order to improve the hardenability, the B content is preferably 0.0001% or more, more preferably 0.0002% or more, and even more preferably 0.0003% or more. It is more preferably 0.0005% or more. It is even more preferably 0.0007% or more. In order to obtain better formability, when B is contained, the B content is preferably 0.0100% or less, more preferably 0.0050% or less, and even more preferably 0.0030% or less.
[0044] Ti:0.200% or less Ti precipitates fine carbides and contributes to increasing strength and trapping hydrogen. There is no particular lower limit for Ti, but in order to obtain these effects, it is preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if Ti is contained in excess, the carbides may become coarse and cause deterioration of bendability. Therefore, if Ti is contained, the Ti content is preferably 0.200% or less, more preferably 0.100% or less, and even more preferably 0.060% or less.
[0045] Nb: 0.200% or less Nb precipitates fine carbides and contributes to increasing strength and trapping hydrogen. There is no particular lower limit for Nb, but in order to obtain these effects, the Nb content is preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if Nb is contained in excess, the carbides may become coarse and cause deterioration of bendability. Therefore, if Nb is contained, the Nb content is preferably 0.200% or less, more preferably 0.100% or less, and even more preferably 0.060% or less.
[0046] Sb: 0.200% or less Sb is an element effective in suppressing excessive decarburization of the steel sheet surface and preventing a decrease in the amount of martensite formed. To obtain such effects, the Sb content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more. On the other hand, in order to obtain better toughness, when Sb is contained, the Sb content is preferably 0.200% or less, more preferably 0.060% or less, and further preferably 0.020% or less.
[0047] Sn: 0.200% or less Sn is an element that is effective in suppressing a decrease in the strength of steel by suppressing decarburization, denitrification, etc. In order to obtain such effects, the Sn content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more. On the other hand, in order to obtain better impact resistance, when Sn is contained, the Sn content is preferably 0.200% or less, more preferably 0.060% or less, and further preferably 0.020% or less.
[0048] V:0.100% or less V precipitates fine carbides, and contributes to increasing strength and hydrogen trapping effect. There is no particular lower limit for V, but in order to obtain these effects, it is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more. The V content is preferably 0.007% or more, and more preferably 0.009% or more. On the other hand, if an excessive amount of V is contained, the carbides may become coarse and cause deterioration of bendability. Therefore, if V is contained, the V content is preferably 0.100% or less, more preferably 0.080% or less, and even more preferably 0.060% or less.
[0049] Cu:2.00% or less Cu is an element that improves hardenability and is effective for setting the area ratio of the hard phase within a more suitable range. To achieve this effect, the Cu content is preferably 0.005% or more, more preferably 0.010% or more, and even more preferably 0.020% or more. The Cu content is preferably 0.040% or more, and more preferably 0.060% or more. Furthermore, when Cu is contained, from the viewpoint of preventing an increase in costs, the Cu content is preferably 2.00% or less, more preferably 1.00% or less, and even more preferably 0.50% or less.
[0050] Cr:2.00% or less The addition of Cr can improve the hardenability and balance between strength and ductility. To obtain this effect, the Cr content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more. The Cr content is preferably 0.007% or more, and more preferably 0.009% or more. Furthermore, when Cr is contained, from the viewpoint of preventing an increase in costs, the Cr content is preferably set to 2.00% or less, more preferably set to 1.00% or less, and further preferably set to 0.80% or less.
[0051] Ni: 2.00% or less The addition of Ni can improve the hardenability and balance between strength and ductility. To obtain this effect, the Ni content is preferably 0.005% or more, more preferably 0.010% or more, and even more preferably 0.020% or more. The Ni content is preferably 0.030% or more, and more preferably 0.040% or more. In addition, when Ni is contained, from the viewpoint of preventing an increase in costs, the Ni content is preferably 2.00% or less, more preferably 1.00% or less, and even more preferably 0.80% or less. The Ni content is preferably 0.60% or less, and more preferably 0.40% or less.
[0052] Mo: 1.00% or less The addition of Mo can provide a strength adjustment effect. To achieve this effect, the Mo content is preferably 0.005% or more, more preferably 0.01% or more, and even more preferably 0.02% or more. The Mo content is preferably 0.03% or more, and more preferably 0.04% or more. When Mo is contained, from the viewpoint of preventing an increase in costs, the Mo content is preferably 1.00% or less, more preferably 0.80% or less, and even more preferably 0.60% or less. The Mo content is preferably 0.50% or less, and more preferably 0.40% or less.
[0053] Ta:0.100% or less The addition of Ta can provide an effect of improving strength. To obtain this effect, the Ta content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.003% or more. Furthermore, when Ta is contained, from the viewpoint of preventing an increase in costs, the Ta content is preferably 0.100% or less, more preferably 0.050% or less, and further preferably 0.020% or less, and preferably 0.010% or less, and more preferably 0.008% or less.
[0054] W: 0.500% or less The addition of W can improve the strength. To achieve this effect, the W content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.003% or more. The W content is preferably 0.005% or more, and more preferably 0.007% or more. In addition, when W is contained, from the viewpoint of preventing an increase in costs, the W content is preferably 0.500% or less, more preferably 0.450% or less, and even more preferably 0.400% or less. The W content is preferably 0.350% or less, and more preferably 0.300% or less.
[0055] Zr: 0.020% or less The addition of Zr can improve the ultimate deformability of the steel sheet and improve the stretch flangeability. To achieve this effect, the Zr content is preferably 0.0005% or more, more preferably 0.0010% or more, and even more preferably 0.0015% or more. In addition, when Zr is contained, from the viewpoint of preventing an increase in costs, the Zr content is preferably 0.020% or less. The Zr content is more preferably 0.010% or less, and even more preferably 0.0050% or less.
[0056] Ca:0.0200% or less By containing Ca, the morphology of sulfides can be controlled, and ductility and toughness can be further improved. In order to obtain better ductility, when Ca is contained, the Ca content is preferably 0.0200% or less. The Ca content is more preferably 0.0100% or less, and further preferably 0.0050% or less. The Ca content is preferably 0.0040% or less, and preferably 0.0030% or less. The lower limit of the Ca content is not particularly limited and may be 0.0000%, but due to restrictions on production technology, the Ca content is preferably 0.0001% or more. From the viewpoint of controlling the morphology of the above-mentioned sulfides and further improving ductility and toughness, the Ca content is more preferably 0.0005% or more.
[0057] Mg: 0.0200% or less The Mg content of 0.0001% or more can control the morphology of sulfides and improve ductility and toughness, more preferably 0.0005% or more, and further preferably 0.001% or more. In order to obtain better ductility, when Mg is contained, the Mg content is preferably 0.0200% or less, more preferably 0.0100% or less, and further preferably 0.0050% or less.
[0058] Zn: 0.020% or less The addition of Zn can improve the ultimate deformability of the steel sheet and improve the stretch flangeability. To achieve this effect, the Zn content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.003% or more. Furthermore, when Zn is contained, from the viewpoint of preventing an increase in costs, the Zn content is preferably 0.020% or less, more preferably 0.010% or less, and further preferably 0.008% or less.
[0059] Co:0.020% or less The addition of Co can improve the ultimate deformability of the steel sheet and improve the stretch flangeability. To achieve this effect, the Co content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.003% or more. When Co is contained, the Co content is preferably 0.020% or less from the viewpoint of preventing an increase in costs. The Co content is more preferably 0.010% or less, and even more preferably 0.008% or less.
[0060] Content of Ce, Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi, REM (excluding Ce): 0.0200% or less The addition of these elements can improve the ultimate deformability of the steel sheet and improve the stretch flangeability. To achieve this effect, it is preferable to contain at least one of these elements in an amount of 0.0001% or more. On the other hand, from the viewpoint of preventing an increase in costs, when at least one of these elements is contained, the content of each is preferably 0.0200% or less. Ce is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Ce is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Ce is preferably 0.0080% or less, and even more preferably 0.0060% or less. Se is preferably 0.0002% or more, and more preferably 0.0005% or more. Se is preferably 0.0007% or more, and more preferably 0.0009% or more. Se is preferably 0.0150% or less, and more preferably 0.0100% or less. Se is preferably 0.0080% or less, and more preferably 0.0060% or less. Te is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Te is preferably 0.0007% or more, and even more preferably 0.0009% or more. Te is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Ge is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Ge is preferably 0.0007% or more, and even more preferably 0.0009% or more. Ge is more preferably 0.0150% or less, and even more preferably 0.0100% or less. As is more preferably 0.0002% or more, and even more preferably 0.0005% or more. As is preferably 0.0007% or more, and even more preferably 0.0009% or more. As is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Sr is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Sr is preferably 0.0007% or more, and even more preferably 0.0009% or more. Sr is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Cs is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Cs is preferably 0.0007% or more, and even more preferably 0.0009% or more. Cs is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Hf is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Hf is preferably 0.0007% or more, and even more preferably 0.0009% or more. Hf is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Pb is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Pb is preferably 0.0007% or more, and even more preferably 0.0009% or more. Pb is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Pb is preferably 0.0080% or less, and even more preferably 0.0060% or less. Bi is more preferably 0.0002% or more, and even more preferably 0.0005% or more. Bi is preferably 0.0007% or more, and even more preferably 0.0009% or more. Bi is more preferably 0.0150% or less, and even more preferably 0.0100% or less. Bi is preferably 0.0080% or less, and even more preferably 0.0060% or less. The REM is more preferably 0.0002% or more, and even more preferably 0.0005% or more. The REM is preferably 0.0007% or more, and even more preferably 0.0009% or more. The REM is more preferably 0.0150% or less, and even more preferably 0.0100% or less. The REM specified in the present invention excludes the above-mentioned Ce. In the present invention, REM refers to scandium (Sc), which has atomic number 21, yttrium (Y), which has atomic number 39, and the lanthanoids ranging from lanthanum (La), which has atomic number 57, to lutetium (Lu), which has atomic number 71. The REM concentration in the present invention refers to the total content of one or more elements selected from the above-mentioned REMs. The REM is not particularly limited, but is preferably Sc, Y or La.
[0061] <Manufacturing method of zinc-plated steel sheet> Next, a method for producing a galvanized steel sheet according to an embodiment of the present disclosure will be described. Note that the temperatures when heating or cooling a steel slab (steel material), a steel sheet, etc. shown below refer to the surface temperatures of the steel slab (steel material), a steel sheet, etc., unless otherwise specified.
[0062] The method for producing a galvanized steel sheet of the present invention includes a hot rolling step of heating a slab having the above-mentioned chemical composition to a temperature range of 1100 to 1350°C, hot rolling the slab at a finish rolling end temperature of 800 to 950°C, and coiling the slab at a coiling temperature of 650°C or less, a heating step of heating the steel sheet after the hot rolling step to 600°C or more in an oxidizing atmosphere containing an oxygen concentration of 1000 volume ppm or more and 30000 volume ppm or less, an oxidation step of holding the steel sheet after the oxidation step in a reducing atmosphere at 700°C or more, a dew point of -20°C or less and a hydrogen concentration of 8 volume % or more and 30 volume % or less for 20 s or more, a reduction step of holding the steel sheet after the reduction step in a reducing atmosphere at 750°C or more, a dew point of -20°C or less. the first cooling process for cooling the steel sheet after the soaking process; a galvanizing process for forming a galvanized layer on the surface of the steel sheet after the first cooling process; a second cooling process for cooling the steel sheet after the galvanizing process at an average cooling rate of 20°C / s or less from a temperature range of 350°C to 450°C to (Ms point - 100°C) and by retaining the steel sheet in a temperature range of 100 to 200°C for 5 seconds or more to a cooling stop temperature of 100°C or less; and a reheating process for retaining the steel sheet after the second cooling process in a temperature range of 100 to 450°C for 5 to 600 s.
[0063] [Hot rolling process] The slab is hot-rolled under the following conditions.
[0064] Slab heating temperature: 1100~1350℃ In order to dissolve carbides and reduce the rolling load, the slab heating temperature is set to 1100° C. or higher. The slab heating temperature is preferably 1150° C. or higher. In order to prevent an increase in scale loss, the slab heating temperature is set to 1350° C. or lower, and preferably 1300° C. or lower.
[0065] Finish rolling temperature: 800~950℃ If the finish rolling end temperature is less than 800°C, ferrite transformation occurs during rolling, and extended ferrite is generated on the surface layer of the hot-rolled sheet, which may remain in the next process and deteriorate the final bendability. Therefore, the finish rolling end temperature is 800°C or higher, preferably 850°C or higher. On the other hand, if the finish rolling end temperature exceeds 950°C, the crystal grains become coarse, which may cause insufficient strength and deterioration of bendability. Therefore, the finish rolling end temperature is 950°C or lower, preferably 930°C or lower.
[0066] Winding temperature: 650℃ or less If the coiling temperature exceeds 650°C, the carbides in the hot-rolled steel sheet will become coarse and will not completely melt before the soaking step, which may cause deterioration in bendability. Therefore, the coiling temperature is 650°C or less, and preferably 600°C or less. There is no particular lower limit to the coiling temperature, but from the viewpoint of suppressing the occurrence of defective shape of the steel sheet and preventing the steel sheet from becoming excessively hard, it is preferably 400°C or more.
[0067] [Cold rolling process (optimal conditions)] Before the steel sheet after the hot rolling process (hot rolling process) is subjected to the oxidation process, cold rolling may be performed as necessary. When cold rolling is performed, it is preferable to perform pretreatment such as pickling and degreasing on the hot rolled steel sheet obtained after the hot rolling process (hot rolling process) by a known method, and then perform the cold rolling under the following conditions.
[0068] Reduction of 20% or more When cold rolling is performed, the reduction ratio (cumulative reduction ratio) is not particularly limited, but if the reduction ratio (cumulative reduction ratio) of cold rolling is less than 20%, the recrystallization of ferrite is not promoted, unrecrystallized ferrite remains, and the steel structure of the present invention may not be obtained. Therefore, the reduction ratio (cumulative reduction ratio) in the cold rolling process is preferably 20% or more, more preferably 30% or more. The upper limit of the reduction ratio is not particularly limited, but the reduction ratio is preferably 80% or less.
[0069] [Oxidation process (optimal conditions)] The oxidation step is a step necessary for improving the wettability of the steel sheet during immersion in hot-dip galvanizing in the galvanizing step, etc., and for obtaining a good appearance. By carrying out oxidation treatment in the oxidation step, an iron oxide layer is formed on the steel sheet surface, and a reduced iron layer is generated during the subsequent annealing in a reducing atmosphere, thereby improving the wettability of the steel sheet.
[0070] Oxygen concentration: 1000 ppm by volume or more and 30000 ppm by volume or less In order to obtain the iron oxide layer required in the oxidation step, it is necessary to set the oxygen concentration in the oxidation atmosphere within a certain range. If the oxygen concentration is less than 1000 ppm by volume, the formation of the iron oxide layer may be insufficient. Therefore, the oxygen concentration is 1000 ppm by volume or more, preferably 1500 ppm by volume or more. On the other hand, if the oxygen concentration exceeds 30000 ppm by volume, excessive iron oxide is formed, and reduction is not completed before the galvanizing step such as hot-dip galvanizing immersion, and the remaining iron oxide may rather deteriorate the plating wettability. Therefore, the oxygen concentration is 30000 ppm by volume or less, preferably 25000 ppm by volume or less. The oxygen concentration is preferably 22000 ppm by volume or less, more preferably 20000 ppm by volume or less.
[0071] Steel plate temperature (maximum temperature reached during oxidation): 600°C or higher If the steel sheet temperature (maximum temperature reached during oxidation treatment) is less than 600°C, the amount of iron oxide formed on the surface will be small, and the plating wettability in hot-dip plating treatment or the like will be insufficient, and a good appearance may not be obtained. Therefore, the steel sheet temperature (maximum temperature reached during oxidation treatment) is 600°C or higher, and preferably 620°C or higher. There is no particular limit to the upper limit of the steel sheet temperature, but in order to more suitably prevent excessive oxidation of the steel sheet, which would result in unreduced iron oxide remaining in the subsequent reduction step, and to more stably obtain excellent plating properties, the upper limit is preferably 900°C or lower, and more preferably 880°C or lower. The steel sheet temperature in the oxidation step (maximum temperature reached during oxidation treatment) is preferably 860°C or lower, and more preferably 840°C or lower.
[0072] [Reduction process] The surface iron oxide formed in the oxidation process is heated in an iron reducing atmosphere to form a reduced iron layer. In the next soaking process, the hydrogen concentration in the atmosphere is relatively low, slowing down the iron reduction reaction rate. Therefore, it is necessary to complete the reduction of the iron oxide in the reduction process.
[0073] Steel plate temperature (maximum temperature reached during reduction treatment): 700°C or higher If the steel sheet temperature (maximum temperature reached during reduction treatment) is less than 700°C, the reduction rate is slow and unreduced iron oxide may remain. Therefore, the steel sheet temperature in the reduction step is 700°C or higher, and preferably 750°C or higher. There is no particular upper limit to the steel sheet temperature, but it is preferably 950°C or lower from the viewpoint of reducing the load on the furnace body. The steel sheet temperature in the reduction step is preferably 920°C or lower, and more preferably 900°C or lower.
[0074] Holding time (holding time during reduction treatment): 20 seconds or more If the holding time in the reduction step (holding time during reduction treatment) is less than 20 seconds, the reduction of the iron oxide may not be completed. Therefore, the holding time in the reduction step is 20 seconds or more, and preferably 25 seconds or more. The upper limit of the retention time is not particularly limited, but from the viewpoint of productivity, it is preferably 150 seconds or less, more preferably 120 seconds or less, and even more preferably 100 seconds or less.
[0075] Hydrogen concentration (hydrogen concentration during reduction treatment): 8% by volume or more and 30% by volume or less If the hydrogen concentration in the atmosphere during the reduction step (hydrogen concentration during reduction treatment) is less than 8 volume %, unreduced iron oxide may remain. Therefore, the hydrogen concentration during the reduction step is 8 volume % or more, and preferably 10 volume % or more. On the other hand, if the hydrogen concentration exceeds 30% by volume, the reduction rate becomes saturated and the penetration of hydrogen into the steel increases excessively, which may make it difficult to sufficiently reduce the amount of hydrogen in the steel in the subsequent soaking step. Therefore, the hydrogen concentration in the reduction step is 30% by volume or less, and preferably 28% by volume or less. The hydrogen concentration is preferably 26% by volume or less, and more preferably 24% by volume or less.
[0076] Dew point (dew point during reduction treatment): -20℃ or less If the dew point of the atmosphere in the reduction step exceeds -20°C, the decarburization reaction on the steel sheet surface may be accelerated, and the galvanized steel sheet of the present invention may not be obtained. Therefore, the dew point of the atmosphere in the reduction step (dew point during reduction treatment) is -20°C or lower, and preferably -25°C or lower. There is no particular lower limit for the dew point, but from the viewpoint of ease of industrial control, -50°C or higher is preferable.
[0077] [Soaking process] In the soaking step, annealing is carried out to obtain the structure of the steel sheet of the present invention, and the hydrogen that has entered the steel in the reduction step is reduced.
[0078] Steel plate temperature (annealing temperature): 750℃ or higher If the steel sheet temperature (annealing temperature) in the soaking step is less than 750°C, the steel sheet surface may be reoxidized. In addition, unrecrystallized ferrite may remain or austenite may not be sufficiently generated during annealing, which may result in failure to obtain the structure required for the galvanized steel sheet of the present invention. Therefore, the steel sheet temperature is 750°C or higher, and preferably 760°C or higher. On the other hand, the upper limit of the steel sheet temperature in the soaking step is not particularly limited, but from the viewpoint of reducing the load on the furnace body and preventing excessive coarsening of austenite grains, it is preferably 950° C. or less. The annealing temperature is preferably 930° C. or less, more preferably 910° C. or less.
[0079] Holding time (holding time during soaking): 20s to 300s If the holding time in the soaking step is less than 20 seconds, hydrogen in the steel may not be sufficiently reduced. Also, the formation of austenite may be insufficient, and the steel structure of the present invention may not be obtained. Therefore, the holding time is 20 seconds or more, and preferably 50 seconds or more. On the other hand, if the holding time exceeds 300 s, the austenite grains will become coarse and the surface layer will become decarburized, and the steel structure of the present invention may not be obtained. Therefore, the holding time is 300 s or less, preferably 200 s or less. The holding time is preferably 180 s or less, more preferably 160 s or less.
[0080] Hydrogen concentration (hydrogen concentration during soaking): 0.2% by volume or more and 8% by volume or less Since the reduction of iron oxide is completed in the reduction process, the hydrogen concentration in the soaking process is set to a low level within a range in which the reduced iron is not reoxidized, thereby reducing the amount of hydrogen that has entered the steel in the reduction process. If the hydrogen concentration exceeds 8% by volume, the hydrogen in the steel cannot be sufficiently reduced, and the steel sheet of the present invention cannot be obtained. Therefore, the hydrogen concentration is 8% by volume or less, and preferably 5% by volume or less. On the other hand, if the hydrogen concentration is less than 0.2% by volume, there is a risk of reoxidation of the reduced iron. Therefore, the hydrogen concentration in the soaking atmosphere is 0.2% by volume or more, and preferably 0.5% by volume or more. The hydrogen concentration is preferably 0.8% by volume or more, and more preferably 1.0% by volume or more.
[0081] Dew point (dew point during soaking): -20℃ or less If the dew point of the atmosphere in the reduction step exceeds -20°C, the decarburization reaction on the steel sheet surface may be accelerated, and the steel sheet of the present invention may not be obtained. Therefore, the dew point of the atmosphere in the reduction step is -20°C or lower, and preferably -25°C or lower. There is no particular lower limit for the dew point, but from the viewpoint of ease of industrial control, -50°C or higher is preferable.
[0082] [First cooling process] The steel sheet after the soaking step is cooled, for example, to a temperature at which it can be immersed in hot-dip galvanizing. The cooling conditions are not necessarily limited, but it is preferable to perform the cooling under the following conditions.
[0083] Hydrogen concentration (hydrogen concentration during first cooling process): 0.5% by volume or more and 30% by volume or less, dew point (dew point during first cooling process): 0°C or less (optimal conditions) Reoxidation during cooling can be suppressed by setting the hydrogen concentration in the cooling atmosphere in the first cooling step to 0.5% by volume or more and the dew point to 0° C. or less. More preferably, the hydrogen concentration is 1.0% by volume or more and the dew point is −20° C. or less. The hydrogen concentration is preferably 1.5% by volume or more, and more preferably 2.0% by volume or more. The dew point is preferably -25°C or lower, and more preferably -30°C or lower. In addition, the lower limit of the dew point is not particularly limited, but the dew point is preferably −55° C. or higher, and more preferably −50° C. or higher. On the other hand, by setting the hydrogen concentration to 30% by volume or less, it is possible to suppress an increase in hydrogen in the steel due to hydrogen penetration during the cooling process. The hydrogen concentration is more preferably 20% by volume or less, and further preferably 10% by volume or less.
[0084] From a steel plate temperature of 600-900°C (steel plate temperature during the first cooling process), cool to 150-500°C at an average cooling rate (average cooling rate during the first cooling process): 20°C / s or less (optimal conditions) In order to more effectively prevent an increase in the amount of hydrogen in the steel during cooling, it is preferable to cool the steel sheet from a temperature of 600° C. to 900° C. at an average cooling rate of 20° C. / s or less. The average cooling rate is preferably 10° C. / s or more. Furthermore, since it is necessary to cool the steel sheet temperature in the subsequent galvanizing process to the same temperature as the galvanizing bath temperature, the cooling stop temperature (cooling stop temperature during the first cooling period) is 500°C or less. If the cooling stop temperature is less than 150°C, excessive martensitic transformation occurs before the galvanizing process, and this is tempered after the galvanizing process, which may result in insufficient strength of the final structure, so the cooling stop temperature is 150°C or more. Here, the average cooling rate (°C / s) is obtained by (steel plate temperature (600 to 900°C)-cooling stop temperature (150 to 500°C)) / cooling time (s) from the start of cooling to the end of cooling.
[0085] [Zinc plating process] A zinc coating layer is formed on the surface of the steel sheet after the first cooling process. A typical method is to immerse the steel sheet in a hot-dip galvanizing bath. In the following, immersion in a hot-dip galvanizing bath will be described as an example.
[0086] The conditions for immersion in the hot-dip galvanizing bath are not particularly limited, and may be performed by a general method. The hot-dip galvanizing bath is composed of Al, Zn, and inevitable impurities, and the composition is not particularly specified. In one example, the Al concentration in the bath may be 0.05 mass% or more and 0.190 mass% or less. If the Al concentration in the bath is 0.05 mass% or more, the occurrence of bottom dross can be more suitably prevented. If the Al concentration in the bath is 0.190 mass% or less, the occurrence of top dross can be more suitably prevented. From the viewpoint of cost, it is preferable to set the Al concentration in the bath to 0.190 mass% or less. The plating bath temperature is not particularly specified, but may be 440°C or more and 500°C or less. The zinc plating applied in the present invention is not limited to the hot-dip galvanizing described above, and may be other methods such as electrogalvanizing or electrogalvanizing, as long as the desired steel sheet temperature is satisfied in the steps before and after the hot-dip galvanizing.
[0087] The plating weight per side is not particularly limited, but in one example, it is 25 g / m 2 More than 120g / m 2 The plating weight per side is 25g / m 2 If the coating weight is 120 g / m or more, the corrosion resistance is particularly good and the coating weight is particularly easy to control. 2 The coating adhesion is particularly good if the coating weight is below 100%. The method for adjusting the coating weight is not particularly limited, but as an example in the case of hot-dip galvanizing, gas wiping is used and the coating weight can be adjusted by adjusting the gas pressure and the distance between the wiping nozzle and the steel sheet.
[0088] In the galvanizing process, after forming a galvanized layer, an alloying process may be performed to obtain a galvannealed steel sheet. By forming the galvanized layer into an alloyed galvanized layer, it is possible to further promote the desorption of hydrogen from the steel in the subsequent reheating process. The conditions of the alloying process are not particularly limited as long as a desired degree of alloying is obtained. For example, in the alloying process in hot dip galvanizing, it is preferable to hold the steel sheet at a predetermined temperature for a predetermined time. For example, the steel sheet temperature can be 440°C or higher. The steel sheet temperature can be 600°C or lower. The holding time can be 5s or more. The holding time can be 60s or less.
[0089] When alloying treatment is performed, the Fe content (degree of alloying) in the plating layer is preferably 7% by mass or more. In addition, this Fe content (degree of alloying) is preferably 15% by mass or less. By setting the degree of alloying to 7% by mass or more, no η-Zn phase remains in the alloyed galvanized layer, and hydrogen in the steel can be more suitably reduced in the reheating step. In addition, if the degree of alloying exceeds 15% by mass, the formation of Γ phase at the interface between the alloyed galvanized layer and the base steel sheet may be promoted, resulting in a decrease in plating adhesion, so that the degree of alloying is preferably 15% by mass or less.
[0090] [Second cooling process] The steel sheet after the above-mentioned galvanizing process is cooled to a cooling stop temperature of 100° C. The cooling method is not particularly limited as long as it satisfies the following cooling conditions, and may be, for example, N2 gas cooling, water cooling, or a combination of these.
[0091] Cooling stop temperature (cooling stop temperature during the second cooling process): 100°C or less In the second cooling step, the untransformed austenite is cooled to a temperature range lower than the Ms point to generate martensite. Compared to austenite with an FCC crystal structure, the hydrogen diffusion rate is faster in martensite with a BCT crystal structure, so that hydrogen reduction in the subsequent reheating step can be promoted. As described above, the steel plate of the present invention needs to be controlled so that 75% or more of the total martensite contained in the structure is tempered martensite having carbides of a predetermined size, and this cannot be satisfied at a cooling stop temperature of more than 100°C. Therefore, the cooling stop temperature is 100°C or less, preferably 80°C or less. As described above, the steel plate of the present invention may have 0% retained austenite, so all untransformed austenite may be transformed into martensite at this point. Therefore, the lower limit of the cooling stop temperature is not particularly limited, but from the viewpoint of industrial ease of implementation, the cooling stop temperature is, for example, 0°C or more.
[0092] Average cooling rate from the temperature range of 350 to 450°C to (Ms point - 100°C) (average cooling rate during the second cooling process): 20°C / s or less In the second cooling step, it is preferable to cool so that the temperature remains in a range of Ms or less and above the cooling stop temperature for a predetermined time. This allows the martensite formed just below the Ms point to self-temper during cooling, and the formation of carbides in the martensite required for the present invention to be further promoted. If the average cooling rate exceeds 20°C / s, self-tempering becomes insufficient and the carbides cannot be obtained sufficiently. Therefore, the average cooling rate is 20°C / s or less, preferably 10°C / s or less, and more preferably 5°C / s or less. Furthermore, although there is no particular lower limit to the cooling rate, a cooling rate of 1° C. / s or more is preferable from the viewpoint of more reliably preventing the carbide size (average grain size of carbides contained in martensite) from exceeding 200 nm due to excessively slow cooling. Here, the average cooling rate (°C / s) is obtained from "(cooling start temperature (350 to 450°C)) - (Ms - 100°C)) / cooling time (s) from the start of cooling to (Ms - 100°C)".
[0093] Stay in the temperature range of 100 to 200°C for 5 seconds or more In the second cooling step, if the residence time in the temperature range of 100 to 200°C is less than 5 seconds, self-tempering is insufficient and the carbides are not sufficiently generated. Therefore, the residence time is 5 seconds or more, preferably 10 seconds or more, and more preferably 20 seconds or more. In order to more stably prevent the carbide size from exceeding 200 nm, the residence time is preferably 100 seconds or less, and more preferably 80 seconds or less.
[0094] The Ms point is the martensitic transformation start temperature and can be calculated by the following formula. Ms(℃)=539-423×{[C mass%]×100 / (100-[α area%])}-30×[Mn mass%]-12×[Cr mass%]-18×[Ni mass%]-8×[Mo mass%] In the above formula, [M mass %] (M: element) is the amount of each element contained in the steel sheet, and [α area %] is the ferrite area ratio (%) in the steel sheet structure after annealing.
[0095] [Reheating process] In this step, the steel sheet from the second cooling step is reheated to temper the martensite necessary for obtaining the steel sheet of the present invention, and at the same time, diffusible hydrogen is reduced.
[0096] In the reheating step, since a zinc-coated layer is already present on the surface of the steel sheet, there is no need to consider iron reoxidation as in the soaking step, and the reheating step can be performed in an atmosphere with a low hydrogen concentration, for example, in the air. On the other hand, if the hydrogen concentration is excessively high, the diffusible hydrogen remaining in the steel will not be reduced, and if the hydrogen concentration is excessively high, there is a risk that it will actually increase again. Therefore, although there are no particular limitations, it is preferable that the hydrogen concentration in the reheating step be 0.2 volume % or less.
[0097] Reheating temperature: 100℃ or higher and 450℃ or lower If the reheating temperature is less than 100°C, the tempering of the martensite is insufficient, and the carbides and tempered martensite required for the present invention cannot be obtained. In addition, if the temperature is less than 100°C, the effect of reducing diffusible hydrogen in the steel is also insufficient. Therefore, the reheating temperature is 100°C or higher, and preferably 120°C. On the other hand, if the reheating temperature is more than 450°C, excessive tempering leads to a decrease in tensile strength and coarsening of carbides, and the steel sheet of the present invention cannot be obtained. In addition, if the temperature is more than 450°C, the appearance of the zinc plating may be impaired. Therefore, the reheating temperature is 450°C or lower, and preferably 430°C or lower.
[0098] Holding time (holding time during reheating): 5 to 600 seconds If the holding time is less than 5 seconds, the tempering of the martensite is insufficient, the carbides and tempered martensite required for the present invention are not obtained, and the diffusible hydrogen in the steel is not sufficiently reduced. Therefore, the holding time is 5 seconds or more, preferably 10 seconds or more. The holding time is more preferably 15 seconds or more, more preferably 20 seconds or more. On the other hand, if the holding time exceeds 600 s, not only will the production efficiency decrease, but excessive tempering will cause a decrease in tensile strength and coarsening of carbides, and the steel sheet of the present invention may not be obtained. Therefore, the holding time is 600 s or less, preferably 500 s or less. The holding time is more preferably 400 s or less, more preferably 300 s or less.
[0099] The production conditions other than those mentioned above can be the same as those in the ordinary methods.
[0100] The plate thickness is not particularly limited, but is preferably 0.4 mm or more, more preferably 0.6 mm or more, and is preferably 3.2 mm or less, more preferably 3.0 mm or less.
[0101] <Materials> Next, a member according to one embodiment of the present invention will be described. A member according to one embodiment of the present invention is a member made of the above-mentioned galvanized steel sheet (as a raw material). For example, the raw material galvanized steel sheet is subjected to at least one of forming and joining to form a member. Here, the above-mentioned galvanized steel sheet has a high yield ratio (YR), excellent bendability, excellent hydrogen embrittlement resistance, and a tensile strength (TS) of 980 MPa or more and less than 1470 MPa. Therefore, the member according to one embodiment of the present invention has a high yield ratio (YR), excellent bendability, excellent hydrogen embrittlement resistance, and a tensile strength (TS) of 980 MPa or more and less than 1470 MPa. Therefore, the member according to one embodiment of the present invention is particularly suitable as a member used in the automotive field.
[0102] <Method of manufacturing components> Next, a method for manufacturing a member according to one embodiment of the present invention will be described. A method for manufacturing a component according to one embodiment of the present invention includes a step of subjecting the above-mentioned zinc-plated steel sheet (e.g., a zinc-plated steel sheet manufactured by the above-mentioned method for manufacturing a zinc-plated steel sheet) to at least one of forming and joining to form a component. Here, the molding method is not particularly limited, and for example, a general processing method such as press processing can be used. The joining method is also not particularly limited, and for example, general welding such as spot welding, laser welding, and arc welding, rivet joining, crimp joining, etc. The molding conditions and joining conditions are not particularly limited, and may be in accordance with ordinary methods. EXAMPLES
[0103] The present invention will be specifically described with reference to examples, but the scope of the present invention is not limited to the following examples.
[0104] Using cold-rolled steel sheets having a thickness of 1.4 mm and having the chemical composition shown in Table 1, hot-dip galvanized steel sheets and galvannealed steel sheets were produced under the conditions shown in Table 2, and the following evaluations were carried out. For all steel sheets, in the hot rolling process, the slab heating temperature was 1250°C, the finish rolling end temperature was 900°C, and the coiling temperature was 520°C, and in the cold rolling process, the rolling reduction ratio was 50%. The reheating treatment in the reheating process was performed in the air. The evaluation results are shown in Table 3. The zinc plating process (hot-dip galvanizing process) and the alloying process in the zinc plating process were performed under the following conditions. All of the following evaluations were performed within 72 hours after the steel sheet first reached room temperature (40°C or lower) after the reheating process specified in the present invention. Plating bath composition: Zn bath containing 0.13% Al by mass Plating bath temperature: 460℃ Plating coverage range: 30~60g / m -2 ·Alloying temperature: 500~560℃ Alloying range: 8.0-14.0% by mass
[0105] [Table 1]
[0106] [Table 2]
[0107] <Tensile test> From the obtained zinc-coated steel sheet, JIS No. 5 tensile test pieces (JIS Z2201) were taken in the direction perpendicular to the rolling direction, and the strain rate was increased to 10 -3 Tensile tests were conducted in accordance with the JIS Z2241 (2011) standard, which specifies a yield strength (YS), tensile strength (TS), elongation (EL), and yield ratio (YR=YS / TS) were determined. Examples of the present invention were those with a TS of 980 MPa or more and less than 1470 MPa and a YR of 0.60 or more. When the product of EL and TS was 10,000 or more, the TS-EL balance was evaluated as excellent.
[0108] <Structural Observation> Test pieces for microstructure observation were taken from the obtained galvanized steel sheets, and the cross section of the sheet thickness parallel to the rolling direction was polished and then corroded with nital solution. The structure was then photographed using an SEM at a magnification of 1500x in three fields of view in the region from the surface to 1 / 8 of the sheet thickness and in the region from 1 / 8 to 3 / 8 of the sheet thickness. The area fraction of the retained austenite was determined individually by measuring the X-ray diffraction intensity, and the area fraction of the as-quenched martensite was determined by subtracting it from the area fraction of the white area (as-quenched martensite and retained austenite). The area fraction of the retained austenite was determined from the ratio of the integrated X-ray diffraction intensity of the (200), (220), and (311) planes of fcc iron to the integrated X-ray diffraction intensity of the (200), (211), and (220) planes of bcc iron in the 1 / 4 plane of the sheet thickness. The retained austenite was calculated as a volume fraction from the above measurements, but the volume fraction of the retained austenite was taken as the area fraction of the retained austenite, assuming that the retained austenite was three-dimensionally homogeneous. The area ratio of each of the constituent phases was determined from the obtained images by the above-mentioned method. The area ratio of each of the constituent phases in each region was the average value of all the images taken. In addition, an image of the structure of one field of view was taken at a magnification of 5000 times in an area of 1 / 8 to 3 / 8 of the sheet thickness of the steel sheet (base steel sheet) using an SEM, and the number and total area of carbides present inside the prior austenite grains containing the martensite were obtained from the image, and the area per carbide was calculated to obtain the average grain size of the carbides. Here, the average grain size is the average value of the long axis length and the short axis length when approximated as an ellipse. Note that, for one carbide, a region formed integrally without interruption in the SEM image was counted as one carbide for measurement.
[0109] <Quantitative determination of hydrogen in steel> A test piece for hydrogen analysis measuring about 5×30 mm was taken from the obtained galvanized steel sheet, the galvanized layer on the surface was removed using a precision grinder, and the piece was quickly placed in a quartz tube in which the atmosphere was replaced with Ar gas, and heated to 600°C at a heating rate of 200°C / h. The amount of hydrogen released during heating was measured using a gas chromatograph. The integrated value of the amount of hydrogen released in the temperature range from room temperature to 200°C was determined as the "amount of diffusible hydrogen," and the integrated value of the amount of hydrogen released in the temperature range from 350°C to 600°C was determined as the "amount of trapped hydrogen." Note that the specimens with a diffusible hydrogen amount of 0.45 mass ppm or less were considered to be examples of the present invention. Here, the amount of diffusible hydrogen and the amount of trapped hydrogen were measured after the production of the steel sheets was completed.
[0110] <Bending test> From the obtained galvanized steel sheet, a rectangular test piece of 35 mm x 100 mm was taken so that the direction parallel to the rolling direction was the bending test axis, and a 90 degree V-bend test was performed at various bending radii at a stroke speed of 50 mm / s, a pressing load of 10 ton, and a pressing hold time of 5 seconds. After the test, the ridge of the bending apex of the test piece was observed with a 10x magnifying glass, and the minimum bending radius R (mm) at which no cracks of 0.5 mm or more were observed was divided by the sheet thickness t (mm) (t = 1.4 mm) to obtain R / t. Note that the examples of the present invention were those that satisfied any of the following (A), (B), or (C). (A) TS: 980MPa or more but less than 1100MPa and R / t: 5.0 or less (B) TS: 1100MPa or more but less than 1300MPa and R / t: 6.0 or less (C) TS: 1300MPa or more but less than 1470MPa and R / t: 7.0 or less
[0111] <Hydrogen embrittlement resistance evaluation> A test piece of 30 mm x 100 mm was taken from the obtained galvanized steel sheet, a spacer having a plate thickness of 2 mm was sandwiched at both ends, and the center between the spacers was spot-welded to prepare a welded test piece. For spot welding, an inverter DC resistance spot welding machine was used, and a dome-shaped electrode made of chromium copper with a tip diameter of 6 mm was used. The pressure was 380 kgf, the current time was 16 cycles / 50 Hz, and the holding time was 5 cycles / 50 Hz. The welding current value was adjusted to form a nugget diameter according to the TS. The nugget diameter was 3.8 mm when the TS was less than 1250 MPa, and 4.8 mm when the TS was 1250 MPa or more. After leaving it for 24 hours after spot welding, the spacer part was cut off, and the cross section of the nugget was observed and evaluated according to the following criteria, and those ranked 1 or 2 were considered to be in the preferred range of the present invention. Crack Observation Results Rank No cracks: 1 (excellent resistance to hydrogen embrittlement) Only microcracks of 100 μm or less occur: 2 (Excellent resistance to hydrogen embrittlement) Cracks over 100 μm: 3 (poor hydrogen embrittlement resistance)
[0112] [Table 3]
[0113] The galvanized steel sheets of the invention examples had a TS of 980 MPa or more and less than 1470 MPa, a YR of 0.60 or more, and diffusible hydrogen in steel of 0.45 mass ppm or less, and were excellent in bendability and hydrogen embrittlement resistance. The steel sheets of the comparative examples were inferior in at least one of TS, YR, bendability, and hydrogen embrittlement resistance.
[0114] In addition, the components obtained by forming or joining the galvanized steel sheets of the examples of the invention had a TS of 980 MPa or more and less than 1,470 MPa, a YR of 0.60 or more, and diffusible hydrogen in the steel of 0.45 mass ppm or less, and were excellent in bendability and resistance to hydrogen embrittlement. [Industrial Applicability]
[0115] According to the present invention, it is possible to obtain a galvanized steel sheet having a TS of 980 MPa or more and less than 1470 MPa, a yield ratio of 0.60 or more, and excellent bendability and hydrogen embrittlement resistance, which is suitable mainly for use in automobile parts.
Claims
1. A galvanized steel sheet having a base steel sheet and a galvanized layer formed on a surface of the base steel sheet, The base steel sheet is In terms of area ratio, Ferrite: less than 50% The sum of martensite and bainite: 50% or more, A steel structure having a retained austenite content of 10% or less, In terms of area ratio, 75% or more of the martensite is tempered martensite having carbides having an average grain size of 50 nm or more and 200 nm or less; The ratio TM1 / TM2 between the area fraction TM1 of tempered martensite in the entire structure in the region from the surface to 1 / 8 of the plate thickness and the area fraction TM2 of tempered martensite in the entire structure in the region from 1 / 8 to 3 / 8 of the plate thickness is 0.70 or more, The tensile strength is 980 MPa or more and less than 1470 MPa, The yield ratio is 0.60 or more, A zinc-plated steel sheet, in which an integrated value of the amount of hydrogen released when the base steel sheet from which the zinc-plated layer has been peeled off is heated from room temperature to 200°C is 0.45 mass ppm or less.
2. The steel composition of the base steel sheet is, in mass%, C: 0.080% or more and 0.300% or less, Si: 0.01% or more and 2.00% or less, Mn: 1.00% or more and 4.00% or less, P: 0.10% or less, S: 0.0200% or less, Al: 0.003% or more and 0.100% or less, N: 0.0100% or less; The galvanized steel sheet according to claim 1 , wherein the balance consists of Fe and unavoidable impurities.
3. The steel composition further comprises, in mass%, B: 0.0100% or less, Ti: 0.200% or less, Nb: 0.200% or less, Sb: 0.200% or less, Sn: 0.200% or less, V: 0.100% or less, Cu: 2.00% or less, Cr: 2.00% or less, Ni: 2.00% or less, Mo: 1.00% or less, Ta: 0.100% or less, W: 0.500% or less, Zr: 0.020% or less, Ca: 0.0200% or less, Mg: 0.0200% or less, Zn: 0.020% or less, Co: 0.020% or less, Ce: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0200% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less; REM (excluding Ce): at least one selected from the following: 0.0200% or less The galvanized steel sheet according to claim 2, comprising:
4. The galvanized steel sheet according to any one of claims 1 to 3, which satisfies the following (A) and / or (B): (A) The zinc plating layer is a zinc alloy plating layer. (B) When the base steel sheet from which the zinc-plated layer has been peeled off is heated from room temperature to 600°C, the integrated amount of hydrogen released in the temperature range of 350 to 600°C is 0.05 mass ppm or more.
5. A member made using the galvanized steel sheet according to any one of claims 1 to 3.
6. A member formed using the galvanized steel sheet according to claim 4.
7. A hot rolling process in which a slab having the steel composition according to claim 2 or 3 is heated to a temperature range of 1100 to 1350 ° C., hot rolled at a finish rolling end temperature of 800 to 950 ° C., and coiled at a coiling temperature of 650 ° C. or less; An oxidation process in which the steel sheet after the hot rolling process is heated to 600° C. or higher in an oxidizing atmosphere containing an oxygen concentration of 1000 ppm by volume or more and 30000 ppm by volume or less; A reduction process in which the steel sheet after the oxidation process is held in a reducing atmosphere at 700° C. or higher, with a dew point of −20° C. or lower and a hydrogen concentration of 8 vol.% or more and 30 vol.% or less for 20 s or more; a soaking step of holding the steel sheet after the reduction step in a soaking atmosphere at 750° C. or higher, with a dew point of −20° C. or lower and a hydrogen concentration of 0.2 vol.% or higher and 8 vol.% or lower, for 20 s to 300 s; A first cooling step of cooling the steel sheet after the soaking step; A galvanizing step of forming a galvanized layer on the surface of the steel sheet after the first cooling step; A second cooling step in which the steel sheet after the galvanizing step is cooled from a temperature range of 350 to 450 ° C. to (Ms point - 100 ° C.) at an average cooling rate of 20 ° C. / s or less and is retained in a temperature range of 100 to 200 ° C. for 5 seconds or more to a cooling stop temperature of 100 ° C. or less; A reheating process in which the steel sheet after the second cooling process is held in a temperature range of 100 to 450 ° C. for 5 to 600 s; Including, Alternatively, there is provided a method for producing a galvanized steel sheet having a base steel sheet and a galvanized layer formed on a surface of the base steel sheet, the method further satisfying the following (a) and / or (b): the base steel sheet has a steel structure which, in terms of area ratio, is less than 50% ferrite, 50% or more in total of martensite and bainite, and 10% or less retained austenite, wherein 75% or more of the martensite, in terms of area ratio, is tempered martensite having carbides having an average grain size of 50 nm or more and 200 nm or less, TM1 / TM2 which is a ratio of an area ratio TM1 of the tempered martensite in the entire structure in a region from the surface to 1 / 8 of the sheet thickness to an area ratio TM2 of the tempered martensite in the entire structure in a region from 1 / 8 to 3 / 8 of the sheet thickness is 0.70 or more, the tensile strength is 980 MPa or more and less than 1470 MPa, and the yield ratio is 0.60 or more, and an integrated value of the amount of hydrogen released when the temperature of the base steel sheet from which the zinc-plated layer has been peeled off is raised from room temperature to 200°C is 0.45 ppm by mass or less. (a) After the zinc plating step, the zinc plating layer is formed on the surface of the steel sheet, and then the steel sheet is further subjected to an alloying treatment. (b) after the hot rolling step and before the oxidation step, a cold rolling step of cold rolling at a rolling reduction of 20% or more is included.
8. The method for producing a galvanized steel sheet according to claim 7, which satisfies the following (c) and / or (d): (c) In the first cooling step, the steel sheet after the soaking step is cooled from 600 to 900°C to 150 to 500°C at an average cooling rate of 20°C / s or less in an atmosphere having a hydrogen concentration of 0.5 vol% or more and 30 vol% or less and a dew point of 0°C or less. (d) In the second cooling step, the average cooling rate from the temperature range of 350 to 450° C. to (Ms point −100° C.) is 10° C. / s or less, and the material is allowed to dwell in the temperature range of 100 to 200° C. for 10 seconds or more to cool to a cooling stop temperature of 100° C. or less.
9. A method for manufacturing a component, comprising a step of subjecting the galvanized steel sheet according to any one of claims 1 to 3 to at least one of forming and joining to form a component.
10. A method for manufacturing a component, comprising the step of subjecting the galvanized steel sheet according to claim 4 to at least one of forming and joining to form a component.
Citation Information
Patent Citations
HIGH STRENGTH STEEL SHEET HAVING MAXIMUM TENSILE STRENGTH OF >=900 MPa AND HAVING SATISFACTORY DUCTILITY AND DELAYED FRACTURE RESISTANCE, METHOD FOR PRODUCING HIGH STRENGTH COLD ROLLED STEEL SHEET, AND METHOD FOR PRODUCING HIGH STRENGTH GALVANIZED STEEL SHEET
JP2011111671A
Methods for manufacturing galvanized steel sheet and galvannealed steel sheet
JP2018165398A
Steel plate for producing press-hardened parts, press-hardened parts having a combination of high strength and crush ductility, and methods for producing the same
JP2020523473A
High-strength hot-dip galvanized steel sheet and production method thereof
WO2016113788A1
Method for manufacturing high-strength hot-dip galvanized steel sheet, method for manufacturing hot-rolled steel plate for high-strength hot-dip galvanized steel sheet, method for manufacturing cold-rolled steel plate for high-strength hot-dip galvanized steel sheet, and high-strength hot-dip galvanized steel sheet
WO2017090236A1